Cerebrospinal fluid haptoglobin levels and outcome after aneurysmal subarachnoid haemorrhage: Evidence from Mendelian randomization - Gbenga A. Kayode; Loukas Zagkos; Godspower Oboli; Sonya Abraham; Gregory Kato; Quazi Ataher; Evangelia Farmakioti; Lothar Tremmel; Stephen Burgess (PLoS ONE, 2025)
Background Subarachnoid haemorrhage (SAH) poses a life-threatening risk, contributing to half of all haemorrhagic strokes, with aneurysmal SAH (aSAH) affecting approximately 6 individuals per 100,000 annually. Following aSAH, the influx of plasma haptoglobin into the cerebrospinal fluid (CSF) is insufficient to sequester the released free haemoglobin in the subarachnoid space and avoid its neurotoxic effects. Exogenous administration of haptoglobin could be a therapeutic strategy for improving outcomes after aSAH. Methods Using individual level data in the UK Biobank and genetic summary statistics from the largest relevant cohorts, Mendelian randomization analysis was conducted to explore the associations of genetically predicted CSF haptoglobin with the risk of catastrophic aSAH (i.e., fatal aSAH or non-fatal aSAH with at least one of: hemiparesis, aphasia, apraxia, or visual field defects within 7 days) and secondary traits, including stroke-related outcomes and imaging markers of brain swelling. Results Higher levels of genetically predicted CSF haptoglobin was associated with lower risk of catastrophic aSAH in multi-ancestry (OR: 0.79, 95% CI: 0.65 to 0.96, p = 0.019) and White British sample analyses (OR: 0.78, 95% CI: 0.63 to 0.95, p = 0.013), while the lack of association with related traits supported effects specific to outcomes after aSAH. A proof-of-concept analysis showing associations of genetically predicted haptoglobin with haemoglobin in plasma validated the proposed mechanism. Conclusions Using human genetic data, we provide evidence to support a causal role of higher CSF haptoglobin in improving outcomes after aSAH. However, there was no evidence for an effect on the risk of aSAH or related cerebrovascular events. These findings support haptoglobin as a potential treatment in aSAH to mitigate the neurotoxic effects of free haemoglobin and improve outcomes.